Pendidikan Karakter Religius Pada Sekolah Dasar : Sebuah Tinjuan Awal - Yayuk Hidayah; Suyitno Suyitno; Lisa Retnasari; Nufikha Ulfah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
The aim of this study described the idea of religious character education in elementary schools. The researchers used literature studies, namely by examining journals, books, research reports, magazines which used to identify religious character education in elementary schools. In analysing the data, the researchers used Miles and Huberman models which were done by data reduction, display, and conclusion. The results showed that the education character in elementary schools was a strategic effort in order to teach students of the values of religious characters to the next stage. The religious character was based on religious values. The implementation of religious education character faced challenging, for instance, from curriculum, mindset, teacher, principal, or even bureaucracy. For this reason, it was needed to face the problem by involving several parties. To be a good character was not only a task on the campus or formal school, but also in the family. Key words: education character, elementary school, religious character